STIMULASI MINAT MEMBACA MELALUI IMPLEMENTASI LITERASI POJOK BACA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 3 ABIANBASE GIANYAR - Herlyana, Ni Wayan Risca; Suyanta, I Wayan; Wahyuni, Ni Nyoman Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading Corner Literacy is a learning strategy implemented to stimulate students’ reading interest by providing easily accessible reading materials inside the classroom. This study is motivated by the importance of strengthening literacy culture in elementary schools to improve students’ reading interest through enjoyable and sustainable reading habits. The problems examined in this study include: (1) the implementation of reading corner literacy in Indonesian language learning in Grade IV of SD Negeri 3 Abianbase Gianyar, (2) the implications of reading corner literacy on students’ reading interest in Indonesian language subject, and (3) the role of the school in supporting the implementation of reading corner literacy in Grade IV. The purpose of this study is to describe the implementation, implications, and the role of the school in supporting reading corner literacy. The theories used are Jean Piaget’s constructivism theory (1952) and Nurhadi’s contextual learning theory (2002). This study uses a descriptive qualitative approach. The research subjects consist of the principal, Grade IV teacher, and Grade IV students. Data collection techniques include participant observation, semi-structured interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results of the study show that the implementation of reading corner literacy is carried out in three stages, namely planning, implementation, and evaluation. In the planning stage, teachers prepare facilities and reading materials. In the implementation stage, reading activities are conducted for 10–15 minutes before learning begins. In the evaluation stage, teachers observe students’ activeness, reading comprehension, and development of reading interest. The findings also indicate an increase in students’ reading interest, vocabulary mastery, and activeness in literacy activities. In addition, the role of the school, teachers, and principal is very important in creating a conducive and sustainable literacy environment.